Effective and selective oxidation of 2-butanol over Mn supported catalyst systems - Prabu, Kandasamy; Prabu, Marimuthu; Venugopal, Ashok Kumar; Venugopalan, Aswathy Thareparambil; Sandilya, W. V. Y. Sai; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (Applied Catalysis A-General, 2016)
Oxidation of alcohols to their corresponding aldehydes/ketones is an important reaction in industries as well as in academic perspective. Selective oxidation (Selox) of alcohols like methanol, ethanol and propanol are well studied in literature; however, alcohols like butanol, pentanol, octanol is a challenging task. Selective oxidation of 2-butanol to methyl ethyl ketone (MEK) is an important reaction due to its wide range of applications. Herein, we demonstrated the selective oxidation of 2-butanol to MEK over Mn supported on different oxide supports. A series of MnxOy-Al2O3 (MA), MnxOy-CeO2 (MC), MnxOy-ZrO2 (MZ) and MnxOy-SiO2 (MS) catalysts were prepared by co-precipitation followed by hydrothermal method. As synthesised catalysts were characterised by various physico-chemical characterisation techniques. It was found that the presence of Mn3O4 species in MA and MZ catalysts is responsible for maximum catalytic activity towards 2-butanol oxidation. MA catalyst conferred a maximum 2-butanol conversion of 51% and 88% selectivity towards MEK. XPS analysis revealed that Mn in MA catalyst exists in +2 and +3 oxidation states and responsible for 2-butanol oxidation. Moreover it was found that the acidity of the catalyst also plays an important role in catalytic activity. (C) 2016 Published by Elsevier B.V.